The effect of wildlife fences on ungulate vehicle collisions - De Prins, Freja (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Many of Sweden’s roads are fitted with wildlife fences to decrease the risk of ungulate vehicle collisions (UVCs). Nevertheless has it been observed that at the ends of these fences, the number of collisions actually increases. In this thesis, I examined if collision probability decreased with an increasing dis-tance from the fence end. In addition, I examined whether the landscape sur-rounding the fence end and the characteristics of the road influenced this. Lastly, I studied if two wildlife fences between Mellerud and Tösse were suc-cessful in reducing the number of UVCs. To test my hypotheses, I analysed collision data collected all over Sweden between 2008 and 2017. I found that collision probability was highest within the first 100 m from a fence end, and that the decrease in collision probability was not influenced by different landscapes and road types. Only one of the two wildlife fences I studied was able to decrease the number of UVCs, where the collision rate was decreased by up to 78%. This information can be used for planning future mitigation efforts, such as the construction of under- or overpasses.